PERLINDUNGAN HUKUM BAGI KONSUMEN YANG DATA PRIBADINYA DIPERJUAL BELIKAN DI APLIKASI FINTECH PEER-TO-PEER LENDING - Roida Nababan; Nelson Persada Sinaga (Magister Hukum Universitas HKBP Nommensen, 2021)
The influence of globalization brings many influences in the progress of life. The rapid development that can be seen from the era of globalization is the development in the field of information technology, especially financial applications. Applications that are developing in the financial services sector are fintech applications. The increase in the use of fintech applications leads to abuse of the fintech application itself. Misuse of personal data of fintech consumers is by buying and selling personal data of fintech consumers. Facts related to the misuse of consumer personal data in fintech applications for sale are circulating on social media. The sale and purchase of consumer personal data using this fintech application was confirmed by a cybersecurity observer from Vaccines.com, Alfons Tanujaya, to CNN Indonesia. The sale and purchase of consumer personal data has violated Article 4 letter a of Law Number 8 of 1999 concerning Consumer Protection, hereinafter referred to as UUPK which states: